MRI of optic tract lesions: Review and correlation with visual field defects - Fadzli, F.; Ramli, N.; Ramli, N.M. (2013)
Visual field defects are a conglomerate of patterns of visual impairment derived from diseases affecting the optic nerve as it extends from the globe to the visual cortex. They are complex signs requiring perimetry or visual confrontation for delineation and are associated with diverse aetiologies. This review considers the chiasmatic and post-chiasmatic causes of visual disturbances, with an emphasis on magnetic resonance imaging (MRI) techniques. Newer MRI sequences are considered, such as diffusion-tensor imaging. MRI images are correlated with perimetric findings in order to demonstrate localization of lesions in the visual pathway. This may serve as a valuable reference tool to clinicians and radiologists in the early diagnostic process of differentiating causes of various visual field defects in daily practice. (C) 2013 The Royal College of Radiologists. Published by Elsevier Ltd. All rights reserved.